Early results of the Resilia Inspiris aortic valve in the old age patients - a retrospective comparison with the Carpentier Edwards Magna Ease - Shala, Magjun (J Cardiovasc Thorac Res, 2020)
Introduction: The Inspiris Resilia aortic valve® (INSPIRIS) is a pericardial bio-prosthesis with a new sterilization procedure that shows promising results in terms of reduced calcification. Methods: The 30-day mortality and morbidity were analyzed, comparing the INSPIRIS implanted between May 2017 and the end of January 2019, with its "predecessor", the Carpentier-Edwards Perimound Magna Ease (ME). Echocardiography was performed one-week after surgery. 125consecutively operated patients were included (59 INSPIRIS, 66 ME). Results: One patient in the ME group died and one patient in the INSPIRIS group had a complicated postoperative course due to right heart failure. Two patients (one INSPIRIS, one ME patient) suffered a perioperative stroke. The hemodynamic evaluation shows an effective reduction of mean transvalvular pressure gradients after surgery in both groups. INSPIRIS tended to have lower trans-prosthetic pressure gradients (9 mm Hg, Interquartile range [IQR] 11-7 mm Hg versus 12 mm Hg, IQR 15-9 mmHg; P = 0.001), reduced trans-prosthetic blood flow acceleration (209 cm/s, IQR 220-190 cm/s versus227 cm/s, IQR 263-191 cm/s; P = 0.003) and increased permeability indices (57%, IQR 67%- 47% versus42%, IQR 48%-38%; P8%; P < 0.001). Conclusion: There are only few clinical data available from INSPIRIS, and the present analysis confirms good results initial postoperatively with a tendency towards possibly improved hemodynamics compared to ME.